Análise de polimorfismos nos genes do receptor de vitamina D, adiponectina e receptor 1 de adiponectina na retinopatia diabética - Assis, Caroline Severo de (2023)
Diabetic Retinopathy is a microvascular complication of Diabetes Mellitus and is one of the main causes of blindness in the working-age population. Retinopathy is closely related to the control of glycemic targets, the duration of diabetes and other complex clinical and genetic aspects that are still not fully understood. Vitamin D, the adipokine Adiponectin and their respective genetic variants, namely VDR, ADIPOQ and ADIPOR1, play important roles in the context of Type 2 Diabetes Mellitus and its complications and, for this reason, are the subject of interest and study. The objective of this work was to analyze the association between the genotypes of the polymorphisms located in the VDR (rs1544410), Adiponectin (rs266729) and adiponectin receptor 1 (rs7539542) genes and Diabetic Retinopathy with the clinical stages of the disease, clinical, biochemical, anthropometric, physical activity and food consumption. Patients with type 2 Diabetes Mellitus, with at least 5 years of diagnosis were recruited and submitted to retinal examination for clinical classification (with or without retinopathy and disease stage) generating the following experimental groups: without retinopathy (n= 139), with retinopathy (n=221) the second group being subdivided into non-proliferative retinopathy (RDNP) n=144 and proliferative retinopathy (RDP) n=77. Biochemical parameters (blood glucose, glycated hemoglobin, total cholesterol, HDL cholesterol, triglycerides, creatinine), anthropometric data, food intake and physical activity were collected and molecular analyzes were performed to determine the genotypes of the polymorphisms of interest. The genotypic and allelic distribution of the polymorphisms studied did not differ between groups without retinopathy compared to those with retinopathy, RDNP and RDP for all genes. However, the presence of the b allele of rs1544410 (Bb+bb) of the VDR gene was associated with higher levels of fasting glucose (p=0.04) and use of insulin therapy (p=0.01) in the group of patients with retinopathy suggesting that it is indicative of a less effective glycemic control than in carriers of the BB genotype. With regard to adiponectin, the presence of the G allele of the rs266729 polymorphism was a risk factor for limb amputation (p=0.009), and the CC genotype for the rs7539542 polymorphism of the adiponectin receptor 1 was a protective factor against amputation (p=0.045). The results of this work suggest that the genotypes of the polymorphisms rs1544410, rs266729 and rs7539542 in the genes of the Vitamin D receptor, adiponectin and Adiponectin Receptor 1 influence glycemic control and the occurrence of amputation in a population in Northeast Brazil.